Hubungan Pertumbuhan dan Perkembangan Lansia Ditinjau dari Pola Hidupnya - Sharita, Angelina Dabayo Disma; Mahardika, I Ketut; Agustinada, Ariqoh; Fadilah, Irfan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to look at the growth and development of the elderly with their lifestyle. This research uses a literature view which is carried out by looking at several pieces of literature from other articles. The results obtained in this article are that growth and development in the elderly can be balanced with a good or positive lifestyle, one of which is an elderly exercise lifestyle. This lifestyle is balanced by doing exercise for the elderly. Physical benefits include, physical fitness, body balance, breathing, and reduced blood pressure in hypertensive elderly. Psychological benefits include improving sleep quality, insomnia, depression or stress.